HUBUNGAN TINGKAT PENGETAHUAN CLINICAL INSTRUKTUR (CI) DENGAN PELAKSANAAN BIMBINGAN METODE BEDSIDE TEACHING (BST) - Ely Yusma Helda (PAKAR Pendidikan, 2015)
Learning processs in practical clinic is one of those determining the quality of the graduates. Ironically, in its practice, there are still some barriers in the clinical pedagogy such as the limited cases and the limited time for clinical lecturers to teach. It shows the weakness of evaluation system in the process of guidance. This research aims at determining clinical instructure (CI) understanding in relation to the implementation of Bedside Teaching (BST) Method Buidance in RSUP. Dr. Djamil, Padang in 2014. The research is analytical research with cross sectional study. The population is all clinical instructures (CI) in the midwifery ward, surgery ward, and interne ward (67 people in total where all are used as total sampling) The primary data collection was done in July 2014. The data was analyzed by univariat and bivariat methods using chi-square test. The result showed that 67,2% CI have good comprehension but 53,7% CI were lack in undergoing Bedside Teaching (BST) Method guidance. Thus, there is a relation between Clinical Instructure (CI) comprehension level and the implementation of Bedside Teaching (BST) Method guidance. Concerning this, it is expected for RSUP Dr. Djamil to give a training to all CI and to create SPO for the students’ guidance especially about Bedside Teaching (BST) Method guidance.